2002
DOI: 10.1093/embo-reports/kvf096
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous insertion and partitioning of alkaline phosphatase into model lipid rafts

Abstract: Several cell surface eukaryotic proteins have a glycosylphosphatidylinositol (GPI) modification at the C-terminal end that serves as an anchor to the plasma membrane and could be responsible for the presence of GPI proteins in rafts, a type of functionally important membrane microdomain enriched in sphingolipids and cholesterol. In order to understand better how GPI proteins partition into rafts, the insertion of the GPI-anchored alkaline phosphatase (AP) was studied in real-time using atomic force microscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
124
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 139 publications
(148 citation statements)
references
References 28 publications
20
124
0
4
Order By: Relevance
“…For all samples, AFM showed that BIAP spontaneously inserted in the gel, i.e. highly ordered, phase of bilayers [67,68,40]. This spontaneous BIAP insertion into SLBs was in accordance with the observations reported for the insertion of various GPI proteins into biomembranes (see above).…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainssupporting
confidence: 91%
See 4 more Smart Citations
“…For all samples, AFM showed that BIAP spontaneously inserted in the gel, i.e. highly ordered, phase of bilayers [67,68,40]. This spontaneous BIAP insertion into SLBs was in accordance with the observations reported for the insertion of various GPI proteins into biomembranes (see above).…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainssupporting
confidence: 91%
“…Such homogeneous protein distribution was in accordance with the existence of a lateral diffusion only modestly reduced in l o phase as compared to the l d phase [2]. This effect of Chl in enhancing the insertion of BIAP, which also resulted in an increase of the ordered domains size, was further demonstrated by adding Chl-loaded methyl-β-cyclodextrin complexes to DOPC/SM bilayers incubated with the protein [68]. As mentioned earlier, POPC/SM/Chl ternary mixtures are more relevant to the composition of biomembrane domains than DOPC/SM/Chl.…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainssupporting
confidence: 74%
See 3 more Smart Citations